Efeito de diferentes tratamentos de superfície de pinos de fibra de vidro na resistência adesiva de um cimento resinoso autoadesivo - Borges, Marciano de Freitas (2016)
The objective of the present study was to evaluate the bond bond strength of intraradicular glass fiber post submitted to different surface treatments and cemented on the root dentin with resin cement adhesive. 40 straight roots of upper incisors extracted for clinical purposes were used in this research (without treatment, silane, 35% hydrogen peroxide, sodium bicarbonate). The post were cemented with resin cement adhesive relyx U200. Twenty four hours after cementing the post, the root were cut crosswise so then producing 1,0 mm inch specimens. The specimens in the format of hourglass were submitted to microtensile tests in order to obtain the amounts of adhesive strength and also to verify the fracture pattern. Two samples of the control group were prepared for analysis using scanning electron microscopy in order to map the adhesive interface. After data collecting, the samples were submitted to ANOVA and test of Tukey statistical analysis. Therefore, these tests were verify differences in the bond strength and allow descriptive analysis of adhesive interface. There was a statistically significant different between the different glass fiber post surface treatments C, Sil, Per and Bic (p = 0.0018 <0.05). There was a statistically significant different between the regions of root dentin (p = 0.0034 <0.05), respectively, coronal region - (19.1 (± 3.71), 25.6 (± 4.3), 24.4 (± 3.16); 30.2 (± 13.0) - showed the highest bond strength values that the root middle third (14.6 (± 4.6), 12.5 (± 5.0), 10.6 (± 3.3), 10.87 (± 2:48). Within the limits of experimental procedures, it can be concluded that treating the surface of the fiber post with chemical and physical agents increases the bond strength of glass fiber post for independent of root dentin canal.